One-Stage Femoral Osteotomy and Computer-Assisted Navigation Total Knee Arthroplasty for Osteoarthritis in a Patient with Femoral Subtrochanteric Fracture Malunion - C. H. Jason Fan (Case Reports in Orthopedics)
Extra-articular femoral deformity in total knee arthroplasty (TKA) is realigned by either intra-articular correction or extra-articular osteotomy. The more distant the deformity is away from knee joint, the more likely it is corrected by the former method. No report described the use of antegrade cephalomedullary femoral nail to fix the osteotomy followed by computer-assisted navigation TKA. This report described the unusual use of this method to manage a 64-year-old man with femoral subtrochanteric fracture malunion and osteoarthritis of knee. He demonstrated a satisfactory functional outcome and good lower limb alignment.